Balancing Patient Care and Force Protection at Military Medical Treatment Facilities. (19th February 2020) - Nardi, Sean; Ferguson, Brian; Peck, Sean; Ross, Elliot; Walrath, Benjamin
ABSTRACT: Objectives: This study aimed to identify delays of care due to base access security protocols at a stateside military medical treatment facility (MTF) for patients with a time-sensitive medical condition who are seeking emergency medical care at the MTF. Methods: We retrospectively analyzed emergency medical services (EMS) run reports from January 1, 2017 to November 12, 2017 to hospital access points to assess patients who were initially denied access to the MTF. Time from EMS activation until patient delivery at the emergency department, number of time-sensitive complaints, number of time-sensitive conditions, and number of unauthorized access attempts are reported. Results: During the 11-month period of review, 42 delays of care related to EMS activation by the sentry at hospital access points were identified. Of the 42, 14 were associated with a time-sensitive complaint, 2 with time-sensitive conditions, and none were unauthorized access attempts. Conclusion: We identify the potential for patient harm due to delays in care resulting from the security protocols at our MTF. A review of force protection requirements with consideration for their impact on patient safety, especially in cases of time-sensitive conditions, has been conducted.